2020
DOI: 10.1021/acssuschemeng.0c07209
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Ionic Liquid-Mediated Red-Emission Carbon Dots and Their Imaging Application in Living Cells

Abstract: Recently, fluorescent carbon dots (CDs) have emerged as novel carbon nanomaterials in terms of their unique optical properties, robust chemical inertness, and excellent biocompatibility. However, synthesis of efficient red-emission carbon dots (R-CDs) remains highly desirable for sensing applications, especially in the field of bioimaging, on account of their deeper tissue penetration and greater bioimaging capability than CDs with low-wavelength emission. Herein, novel R-CDs are synthesized by one-step solvot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 48 publications
1
8
0
Order By: Relevance
“…The diameter of the as-prepared PET-CDs is in the range from 1.6 to 4.6 nm with an average size of 2.8 nm (Figure b). What is more, it can be seen from the inset of Figure a that the well-resolved lattice spacing of PET-CDs is 0.21 nm, which is consistent with the d -spacing of the graphene (100) planes …”
Section: Resultssupporting
confidence: 74%
“…The diameter of the as-prepared PET-CDs is in the range from 1.6 to 4.6 nm with an average size of 2.8 nm (Figure b). What is more, it can be seen from the inset of Figure a that the well-resolved lattice spacing of PET-CDs is 0.21 nm, which is consistent with the d -spacing of the graphene (100) planes …”
Section: Resultssupporting
confidence: 74%
“…Furthermore, a new and strong stretching vibration of C–S–C at around 1193 cm –1 emerged in the FTIR spectrum of R-GQDs, proving the successful introduction of sulfur element in R-GQDs. The distinct characterization results suggest that the higher graphite nitrogen content and degree of oxidation may be the key for the red shift of fluorescence emission . In order to verify our conjecture, XPS was further employed to survey the surface functionalization and terminal elements of GQDs.…”
Section: Resultsmentioning
confidence: 65%
“…The distinct characterization results suggest that the higher graphite nitrogen content and degree of oxidation may be the key for the red shift of fluorescence emission. 42 In order to verify our conjecture, XPS was further employed to survey the surface functionalization and terminal elements of GQDs. As shown in Figure S7a, the XPS full spectra showed that G-GQDs and R-GQDs contain three typical characteristic peaks of C 1s, N 1s, and O 1s at 285, 399, and 532 eV, while R-GQDs additionally contain an S 2p peak at 164 eV.…”
Section: Resultsmentioning
confidence: 86%
“…2a, the broad absorption bands at 3106–3480 cm −1 were attributed to the stretching vibrations of O–H and N–H. 53 The bands at 1405–1684 cm −1 are the characteristic absorptions of CC, CN, and CO. 34 The absorption bands at 1356–1790 cm −1 correspond to the stretching vibrations of C–N. 54 In addition, the stretching vibrations of PO are located at 884–1032 cm −1 .…”
Section: Resultsmentioning
confidence: 99%
“…Recently, the preparation of CDs using o-phenylenediamine (o-PD) as a carbon source has attracted the attention of many researchers; [34][35][36][37][38][39][40][41][42][43] o-PD can not only dope the CDs with nitrogen atoms to improve their optical properties but also modify the CD surface with amino groups, enabling CDs to detect pH, identify substances, etc. 44,45 However, to the best of our knowledge, there have been no reports on the direct microwavemethod preparation of R-CDs using o-PD as a carbon source to detect extremely low pH values by uorescence enhancement.…”
Section: Introductionmentioning
confidence: 99%